Antimicrobial Drug-Resistant Gram-Negative Saprophytic Bacteria Isolated from Ambient, Near-Shore Sediments of an Urbanized Estuary: Absence of β-Lactamase Drug-Resistance Genes - Charles F. Moritz; Robert E. Snyder; Lee W. Riley; Devin W. Immke; Ben K. Greenfield (Antibiotics, 2020)
We assessed the prevalence of antimicrobial resistance and screened for clinically relevant β-lactamase resistance determinants in Gram-negative bacteria from a large urbanized estuary. In contrast to the broad literature documenting potentially hazardous resistance determinants near wastewater treatment discharge points and other local sources of aquatic pollution, we employed a probabilistic survey design to examine ambient, near-shore sediments. We plated environmental samples from 40 intertidal and shallow subtidal areas around San Francisco Bay (California, USA) on drug-supplemented MacConkey agar, and we tested isolates for antimicrobial resistance and presence of clinically relevant β-lactamase resistance determinants. Of the 74 isolates identified, the most frequently recovered taxa were Vibrio spp. (40%), Shewanella spp. (36%), Pseudomonas spp. (11%), and Aeromonas spp. (4%). Of the 55 isolates tested for antimicrobial resistance, the Vibrio spp. showed the most notable resistance profiles. Most (96%) were resistant to ampicillin, and two isolates showed multidrug-resistant phenotypes: V. alginolyticus (cefotaxime, ampicillin, gentamicin, cefoxitin) and V. fluvialis (cefotaxime, ampicillin, cefoxitin). Targeted testing for class 1 integrons and presence of β-lactam-resistance gene variants TEM, SHV, OXA, CTX-M, and Klebsiella pneumonia carbapenemase (KPC) did not reveal any isolates harboring these resistance determinants. Thus, while drug-resistant, Gram-negative bacteria were recovered from ambient sediments, neither clinically relevant strains nor mobile β-lactam resistance determinants were found. This suggests that Gram-negative bacteria in this well-managed, urbanized estuary are unlikely to constitute a major human exposure hazard at this time.